A revision of Salispina, its placement in a new family, Salispinaceae (Rhipidiales), and description of a fourth species, S. hoi sp. nov - Reuel M. Bennett; Mark Kevin Devanadera; Gina R. Dedeles; Marco Thines (IMA Fungus)
Abstract The genus Salispina was recently described for saprotrophic estuarine oomycetes with aculeolate or spiny sporangia. The genus currently contains three species, S. intermedia, S. lobata, and S. spinosa, the latter two previously included in Halophytophthora. During a survey of mangrove-inhabiting oomycetes in the Philippines, an isolate of Salispina (USTCMS 1611), was obtained from a decaying mangrove leaf. This isolate differed from other species in the genus in a unique combination of morphological and biological characters. Phylogenetic analysis revealed it to be the sister lineage of S. lobata. Consequently, the new species name S. hoi is introduced for the isolate. In addition, Salispina spp. grouped with Sapromyces of Rhipidiales with strong support, but differs from all other known genera of the order in the weak formation of hyphal constrictions, and absence of basal thalli and a holdfast network. The new family Salispinaceae is, therefore, described to accommodate Salispina in the order Rhipidiales.